USING QUIZZES APPLICATION TO IMPROVE STUDENT’S MOTIVATION IN LEARNING ENGLISH AT STTIND PADANG - Christy Jufri, Allen; Warni, Asis (Ensiklopedia of Journal, 2025)
The purpose of this study is to investigate the usage of the learning media Quizizz in English education in order to boost students' motivation to learn at STTIND Padang.  The purpose of this study was to determine the impact of Quizizz on students' motivation and interest in studying, as well as to identify the media's strengths and limitations.  The research approach employed was classroom action research with English Subject for Mining Engineering students.  The research was carried out in numerous cycles, each of which included planning, activity, observation, and reflection.  Data were gathered by observation, interviews, and questionnaires, and were examined qualitatively.  This study found that using Quizizz learning material increases students' motivation and interest in learning. Students are more enthusiastic while learning with Quizizz because they take interactive quizzes and receive fast feedback.  In addition, students are more interested in studying English through this application. This study suggests that using Quizizz learning media in the context of learning English at STTIND Padang can improve learning effectiveness and raise students' motivation to learn.